Validity of Chemistry Comic Learning Media on Reaction Rate Material Integrated with Islamic Values - Lutfiana Marisa; Khairiatul Muna; Muhammad Bahit (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
Reaction rate material requires an understanding of chemical multirepresentations, which is a challenge for students. Although digital comics are increasingly used in learning, research on the integration of Islamic values and multirepresentation in chemical comics is still limited. In addition, the use of Webtoon as a learning platform in science education is still rarely researched. The research aims to find out how the validity of chemical comic learning media on reaction rate materials that are integrated with Islamic values. The research method used is R&D with the ADDIE design model; validation was carried out by experts in media, material, and Islamic integration, with the scores obtained categorized into very valid, valid, invalid, and very invalid using quantitative descriptive analysis. Research with the ADDIE model goes through five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The validity results obtained a score of 89% for media validity, 84% for material validity, and 83% for integration validity with all categories very valid. The results of the study show that the developed comic media is proven to be very valid so that the developed media is suitable for further testing to the Implementation stage.